2023
DOI: 10.1039/d2fo02715a
|View full text |Cite
|
Sign up to set email alerts
|

Honey polyphenols: regulators of human microbiota and health

Abstract: A comprehensive review of research over the last decade was conducted to carry out this work. The main objective of this work is to present relevant evidence of the effect...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 202 publications
(433 reference statements)
0
8
0
Order By: Relevance
“…22 Besides being chemical markers, honey phenolic compounds are beneficial to human health, especially for patients with chronic diseases. 1 Chaste honey contains high levels of phenolic compounds, including apigenin, luteolin, neochlorogenic acid, kaempferide, epi-dihydrophaseic acid, salicylic acid, trans-cinnamic acid, kaempferitrin, quercetin, formononetin, eriodictyol, protocatechuic acid, apigetrin, chrysin, chlorogenic acid, vanillic acid, isoferulic acid, myricetin, ferulic acid, and 4-hydroxybenzoic acid (Table S2). These phenolic compounds are widely reported as common honey constituents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Besides being chemical markers, honey phenolic compounds are beneficial to human health, especially for patients with chronic diseases. 1 Chaste honey contains high levels of phenolic compounds, including apigenin, luteolin, neochlorogenic acid, kaempferide, epi-dihydrophaseic acid, salicylic acid, trans-cinnamic acid, kaempferitrin, quercetin, formononetin, eriodictyol, protocatechuic acid, apigetrin, chrysin, chlorogenic acid, vanillic acid, isoferulic acid, myricetin, ferulic acid, and 4-hydroxybenzoic acid (Table S2). These phenolic compounds are widely reported as common honey constituents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Common characteristic phenolic compounds are utilized as chemical markers for identifying the origin of monofloral honey . Besides being chemical markers, honey phenolic compounds are beneficial to human health, especially for patients with chronic diseases …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main functional components in honey, metabolites crucially contribute to the effects of health benefits of honey . Besides, establishing honey authenticity identification methods based on characteristic phytogenic components has become the object of multiple studies. , Thus, UHPLC-Q-TOF-MS/MS-based metabolomic analysis was conducted to screen characteristic phytogenic components that can discriminate between MH- Sco and other honeys.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotics disrupt this processes by which oral bacteria adhere to proteins, hence inhibiting the production of biofilm. research has shown that probiotics enhance the treatment-induced mucositis 16 .…”
Section: Resultsmentioning
confidence: 99%